2018
DOI: 10.1016/j.bjps.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Are facial injuries really different? An observational cohort study comparing appearance concern and psychological distress in facial trauma and non-facial trauma patients

Abstract: Facial injuries are widely assumed to lead to stigma and significant psychosocial burden. Experimental studies of face perception support this idea, but there is very little empirical evidence to guide treatment. This study sought to address the gap. Data were collected from 193 patients admitted to hospital following facial or other trauma. Ninety (90) participants were successfully followed up 8 months later. Participants completed measures of appearance concern and psychological distress (post-traumatic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Several papers in this review demonstrated female gender to be associated with higher rates of psychopathology [18,23,24], a finding that is in keeping with general population studies (Bottomley et al, 2010;Merikangas et al, 2011). Other work has shown that females score higher on measures of maladaptation to disfigurement than males (Rahtz et al, 2018). Therefore, it may be that there is a composite relationship of female gender and facial scarring in the risk for developing psychopathology.…”
Section: Biassupporting
confidence: 70%
“…Several papers in this review demonstrated female gender to be associated with higher rates of psychopathology [18,23,24], a finding that is in keeping with general population studies (Bottomley et al, 2010;Merikangas et al, 2011). Other work has shown that females score higher on measures of maladaptation to disfigurement than males (Rahtz et al, 2018). Therefore, it may be that there is a composite relationship of female gender and facial scarring in the risk for developing psychopathology.…”
Section: Biassupporting
confidence: 70%
“…According to clinical researches, about 20%-30% patients with facial trauma show the symptoms and signs of anxiety [ 28 , 29 ]. Moreover, patients with facial trauma showed increased PTSD incidence compared with the general population [ 30 , 31 ]. In our study, we found that patients with facial trauma exhibited evident short-term symptoms of depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…8,18 Nonetheless, it is noteworthy that facial trauma patients, many of whom have significant facial disfigurement, report higher satisfaction with facial appearance when compared with patients seeking facial aesthetic surgery. 19 The composition of the “Other” injury mechanism group (gunshots, dogbites, forklift trauma) likely explains their lower scores. It is unclear why longer duration from surgery is associated with lower scores on this scale.…”
Section: Discussionmentioning
confidence: 99%